Synthesis and Preliminary Immunological Evaluation of a Pseudotetrasaccharide Related to a Repeating Unit of the Streptococcus pneumoniae Serotype 6A Capsular Polysaccharide - Sukhova, Elena V.; Yashunsky, Dmitry V.; Kurbatova, Ekaterina A.; Akhmatova, Elina A.; Tsvetkov, Yury E.; Nifantiev, Nikolay E. (Frontiers in Molecular Biosciences, 2021)
2-Aminoethyl glycoside of the pseudotetrasaccharide α-D-Glcp-(1→3)-α-L-Rhap-(1→3)-D-Rib-ol-(5-P-2)-α-D-Galp corresponding to a repeating unit of the Streptococcus pneumoniae type 6A capsular polysaccharide has been synthesized. A suitably protected pseudotrisaccharide α-D-Glcp-(1→3)-α-L-Rhap-(1→3)-D-Rib-ol with a free 5-OH group in the ribitol moiety and a 2-OH derivative of 2-trifluoroacetamidoethyl α-D-galactopyranoside have been efficiently prepared and then connected via a phosphate bridge using the hydrogen phosphonate procedure. Preliminary immunological evaluation of this pseudotetrasaccharide and the previously synthesized pseudotetrasaccharide corresponding to a repeating unit of the capsular polysaccharide of S. pneumoniae serotype 6B has shown that they contain epitopes specifically recognized by anti-serogroup 6 antibodies and are able to model well the corresponding capsular polysaccharides. Conjugates of the synthetic pseudotetrasaccharides with BSA were shown to be immunogenic in mice.